From a hungarian view: the writings of Károly László on Mexico, 1857-1865 (Tzintzun, Revista de Estudios Históricos, 2020)
KaÌroly LaÌszloÌ was a Hungarian exile who resided in Mexico between 1857 and 1865. Chief surveyor, chief engineer, entrepreneur, traveler with personal experience on the Tehuantepec route, American citizen, Hungarian nationalist and prolific writer. He kept a diary during his years as an expatriate and produced some of the first articles that the Hungarian public could read about Mexico. This essay studies the writings of LaÌszloÌ in order to complement the existing sources on the Isthmus of Tehuantepec with both new data and an unusual, east- European perspective.